The Effectiveness of Healthy Romantic Relationship Training on Enhancing Self-Concept Among Emerging Adults - Tobing, Jessica Rosdiana; Ginanjar, Adriana Soekandar; Pranawati, Santy Yanuar (Universitas Negeri Padang, 2024)
Building healthy romantic relationships is a critical developmental task during emerging adulthood as it contributes to higher psychological well-being. However, the instability and uncertainty that often characterize this period can hinder emerging adults from forming healthy romantic relationships. It has been found that self-concept is a key factor in building healthy romantic relationships, as a strong self-concept supports more positive outcomes in romantic relationships. However, much of the existing training only focuses on sexual health education and dating violence. In addition, the majority of emerging adults report that they have not received the relationship education they desire or require, whether from their families or educational institutions. To fill the gap in knowledge about this topic, this study focuses on enhancing self-concept through healthy romantic relationship training. This study hypothesized that participants who completed the training would report higher mean self-concept and healthy romantic relationship knowledge scores. This quasi-experimental study, employing one group pre-test and post-test design, involved 13 participants (M = 21.8, SD = 2.1). The instruments used to measure the variables were the Tennessee Self-Concept Scale Second Version Short Form (TSCS:2 SF) and the Healthy Romantic Relationship Knowledge Questionnaire. Qualitative data were also derived to support the quantitative data. Quantitative analysis using ANOVA Repeated Measures and thematic qualitative analysis showed that healthy romantic relationship training significantly enhanced self-concept in emerging adults. The research implications highlight the significance of providing training on healthy romantic relationship for emerging adults, emphasizing the need to focus on self-concept which can contribute to higher romantic relationship quality.